Optimizing the Public Relations and Government Protocol communication strategy of Bima District Local Government in building a positive image - Tasrif, Tasrif; Haeril, Haeril (The International Journal of Politics and Sociology Research, 2024)
This research examines the role and challenges faced by the Public Relations and Government Protocol Department of Bima District Local Government in optimizing services and interactions with the public amidst the continuously evolving era of digitization and globalization. Employing a qualitative descriptive approach, this study explores the dynamics of communication and government protocol through direct observation, interviews, and document studies. The research findings highlight the importance of the PR function in delivering accurate and responsive information, as well as the role of protocol in ensuring the efficient and ethical implementation of government activities. These functions are crucial in building inclusive, transparent, and participatory relationships between the local government and its constituents. The research also identifies challenges such as the spread of misinformation, the need for human resource capacity building, and underutilization of social media. Thus, this study underscores the urgency of a deep understanding of the dynamics of communication and government protocol in maintaining harmonious relationships with the public and addressing contemporary challenges in the delivery of information and public services.